Hibah dan Korelasinya Dengan Kewarisan; Pemerataan Ekonomi Dengan Prinsip Keadilan Dalam Keluarga - Ahmad Badrut Tamam (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2019)
Some Muslims consider that the provisions in Islamic inheritance law (faraid) cause and separate the problem. Cases of inheritance distribution often end in disputes. In addition to using inheritance law, transfer of ownership of property in Islam can also be done through grants. For parents it is possible to share his wealth with his children and family or other heirs, while he is still alive. Is not that way disputes that occur between heirs can be minimized. It is therefore important to look for correlations between grants and inheritance to realize the equitable distribution of the economy in the family.